C Programming Pocket Primer - Campesato, Oswald (Pocket Primer, 2019)
Introducing advanced beginners to C programming fundamentals, this book will teach you how to write C programs that involve various C data types, loops, conditional logic, built-in functions, custom functions, and recursion. --